Analysis of the impact strength on laminated polyester composites reinforced sugar palm fiber (SPF) with fiber orientation: random and woven - Fatkhurrohman Fatkhurrohman; Machmudi Machmudi (Politeknik Negeri Lhokseumawe, 2022)
Recently, composite materials have attracted the attention of researchers because of their advantages. The utilization of composite materials is widely used in various industrial fields, including in the automotive industry which is used as a car bumper. A car bumper composite material must be resistant to shock loads and good in energy absorption. Due to this, the composite material will be subjected to an impact test. This study aims to analyze the effect of variations in fiber volume fraction on the impact strength of laminated composites with a polyester matrix with sugar palm fiber (SPF) reinforcement with fiber orientation direction: random and woven. Composite fabrication was carried out using the hand layup and press molding methods with variations in fiber volume fractions of 20%, 30%, 40%, 50%, and 60%. Then the Charpy impact test was carried out with ASTM D-6110 standard and analyzed the fracture morphology. The test results show that increasing the fiber volume fraction up to 40% can increase the impact strength. However, the impact strength decreased at 50% and 60% fiber volume fraction. The results of the largest impact test were obtained at the 40% fiber volume fraction of 0.62 J/mm2 while the lowest value at the 20% fiber volume fraction was 0.42 J/mm2. The increase in the impact test value can be due to the uniform distribution of the load by the matrix to the fiber. Based on the morphological analysis carried out through macro photos of the shape of the fracture and the cross-section of the fracture, the results of the impact test showed that fibrous fractures occurred while on the cross-section of the fracture delamination and fiber pullout appeared.